Haplotype-resolved and near-T2T genome assembly of the African catfish (Clarias gariepinus) - Julien A. Nguinkal; Yedomon A. B. Zoclanclounon; Ronald M. Brunner; Yutang Chen; Tom Goldammer (Scientific Data, 2024)
Abstract Airbreathing catfish are stenohaline freshwater fish capable of withstanding various environmental conditions and farming practices, including breathing atmospheric oxygen. This unique ability has enabled them to thrive in semi-terrestrial habitats. However, the genomic mechanisms underlying their adaptation to adverse ecological environments remain largely unexplored, primarily due to the limited availability of high-quality genomic resources. Here, we present a haplotype-resolved and near telomere-to-telomere (T2T) genome assembly of the African catfish (Clarias gariepinus), utilizing Oxford Nanopore, PacBio HiFi, Illumina and Hi-C sequencing technologies. The primary assembly spans 969.62 Mb with only 47 contigs, achieving a contig N50 of 33.71 Mb. Terminal telomeric signals were detected in 22 of 47 contigs, suggesting T2T assembled chromosomes. BUSCO analysis confirmed gene space completeness of 99% against the Actinopterygii dataset, highlighting the high quality of the assembly. Genome annotation identified 25,655 protein-coding genes and estimated 43.94% genome-wide repetitive elements. This data provides valuable genomic resources to advance aquaculture practices and to explore the genomic underpinnings of the ecological resilience of airbreathing catfish and related teleosts.